2014
DOI: 10.1590/0103-6440201300052
|View full text |Cite
|
Sign up to set email alerts
|

Cell Viability of Candida albicans Against the Antifungal Activity of Thymol

Abstract: Candida albicans is a commensal fungus, but circumstantially it may cause superficial infections of the mucous membranes, such as denture stomatitis, when a biofilm is formed on the surface of dental prostheses. This study evaluated the cell viability of C. albicans biofilms against the antifungal activity of thymol when compared with miconazole, by the fluorescence imaging using SYTO 9 and propidium iodide dyes, and counting of colony forming units. C. albicans standard strains (ATCC 11006) were used. The min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 20 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…The potent antibacterial (Karpanen et al, 2008, Didry et al, 1994, Shapiro et al, 1994, Botelho et al, 2007 and antifungal (de Vasconcelos et al, 2014, Pemmaraju et al, 2013 actions of T are well known. Its mechanism of action is based on cell membrane disruption, leakage of intracellular substances, and subsequent changes in transmembrane potential (Shapiro and Guggenheim, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The potent antibacterial (Karpanen et al, 2008, Didry et al, 1994, Shapiro et al, 1994, Botelho et al, 2007 and antifungal (de Vasconcelos et al, 2014, Pemmaraju et al, 2013 actions of T are well known. Its mechanism of action is based on cell membrane disruption, leakage of intracellular substances, and subsequent changes in transmembrane potential (Shapiro and Guggenheim, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Then there is2.69 mM menthol that showed a cytotoxic activity on cell line A-375 at a concentration of 0.012 mM with 50% survival of cells (LC50) (Kijpornyongpan et al, 2014), and that acts on the lipid phase of plasma membrane (Kupisz et al 2015). Listerine thymol concentration is4.3 mM, and besides LC50 at 0.7 mM (Stammati et al, 1999), thymol demonstrated in those lower concentrations its antibacterial capabilities (Shapiro et al, 1994;Didry et al, 1994;Botelho et al, 2007;Karpanen et al 2008) in the Hep-2 cell line (Pemmaraju et al, 2013;de Vasconcelos et al, 2014). It also demonstrated that it affects cell membrane damage and hence the release of intracellular substances and changes in transmembrane potential (Shapiro and Guggenheim, 1995), probably not acting on calcium TRP channel receptors but through mitochondrial damage and stimulation on apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…After this, the samples were incubated at 37 °C for 48 hours, under constant agitation (110 rpm) in an incubator shaker, and washed with phosphate buffer (PBS, pH 7.2 ± 0.1) to remove non-adherent cells (Vasconcelos et al, 2014). The samples were divided into three groups: (i) control group that was not treated; (ii) the group treated with the argon plasma, and (iii) the group treated with argon plus air plasma.…”
Section: Methodsmentioning
confidence: 99%